Peningkatan Produktivitas Petani Sagu melalui Aplikasi Teknologi Mekanisasi Pengolahan Pati Sagu dengan Pemanfaatan Sumber Energi Hybrid - Cipto; Kaikatui, Rapha Nichita; Sariman, Farid; Rusdi, Muhamad (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
The enhancement of sago farmers' productivity is a key focus in supporting food security and empowering the economy of the Papuan people, particularly the indigenous Papuans (OAP). This community partnership service (PKM) activity was conducted with sago farmers in Kweel Village, Merauke, South Papua, aiming to improve the efficiency and quality of sago starch production through the application of mechanization technology utilizing hybrid energy sources, combining renewable and conventional energy. The mechanization technology used includes sago pith shredding machines, sago starch extraction machines, and solar-powered water pumps to facilitate the sago processing. The results of the PKM activity implementation show an increase in farmer productivity, production process efficiency, and improved sago starch quality. Technology transfer to partners was carried out through socialization and training, which enhanced partners' skills in operating mechanized equipment and managing hybrid energy. Additional positive impacts include reduced production costs, shorter working hours, and support for environmental sustainability through the use of eco-friendly energy.